Masa Depan Ketenagakerjaan Indonesia: Perlindungan dan Efektivitas Hukum Bagi Pekerja dalam Menghadapi Transformasi AI - Anisah, Nur Fadiah; Handayani, Septy Amelia; Poernomo, R. Wahjoe; Parameswari, Desak Andini; Sogi, Manggala Nimara; Lisa (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
In the current digital transformation era, many industrial companies are competing to utilize sophisticated technology based on Artificial Intelligence (AI) as a form of digital automation to replace repetitive tasks that aim to reduce dependence on human workers and budget efficiency for companies. This study focuses on the problem of the presence of AI replacing the role of workers because competition is no longer limited to humans between humans, but must also compete with the sophistication of AI technology that is increasingly rapid and in greater needed by companies. This study aims to see how well the Indonesian employment law system is able to handle the challenges of the automation era, which has become an urgent reality and is no longer predictable. This study was compiled using a qualitative method with a literature study approach that aimed to build a critical analysis of digitalization and its impact on employment and industrialization policies. The results of this study showed that digital technology would not deterministically shape a new future, but the choices and logical consequences of a digital work pattern model that was different from the old pattern. The response to industrialization policies in the digital era must be able to answer the wave of disruption for the workforce. Policies in the aspect of education and training for affected workers are an urgency that cannot be ignored in the era of industrial automation.